(untitled) (Cambridge, U.K., 2002)
This book acts as a manifesto for historical sociology, considering a range of issues, including accounts of the major variants of historical sociology, how they can be applied to international relations, why international relations theorists should engage with these approaches, and how historical sociological insight can enhance and reconfigure the study of international relations. In addition to describing the seven major approaches - neo-Weberianism, constructivism, critical historical materialism, critical theory, postmodermism, structural realism and world system theory - the volume's introductory and concluding chapters set out in detail an approach and research agenda that revolve around what the editors call "world sociology".
Keywords: International relations,Historical sociology; Sociological aspects,History